2011
DOI: 10.1038/clpt.2011.87
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and the “Obesity Paradox” in Cardiovascular Diseases

Abstract: Obesity adversely affects most cardiovascular (CV) risk factors and is strongly associated, probably as an independent risk factor, with most CV diseases. However, substantial evidence points to the existence of an "obesity paradox," in that overweight and obese patients with established CV diseases typically have a better prognosis than leaner patients with the same CV disease. Despite this paradox, we believe that the "weight" of evidence still supports efforts at purposeful weight loss in both primary and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 11 publications
1
20
0
Order By: Relevance
“…Finally, it has been suggested that the obesity paradox may be due in part to unintentional weight loss before study entry, leading to a worse prognosis in the normal-weight group during follow-up. 24,25 For example, Strandberg et al, 26 in a long-term follow-up study in 1114 Finnish men, found that subsequent weight decrease among overweight patients and high CVD risk in midlife (mean age, 47 years) predicted the worst prognosis in late life (mean age, 73 years). However, Lavie et al 18 evaluated purposeful weight loss in 529 overweight and obese CHD patients and found that although 3-year mortality risk only trended lower for those who lost weight, several CVD risk factors and behavioral factors were markedly improved.…”
Section: Discussionmentioning
confidence: 96%
“…Finally, it has been suggested that the obesity paradox may be due in part to unintentional weight loss before study entry, leading to a worse prognosis in the normal-weight group during follow-up. 24,25 For example, Strandberg et al, 26 in a long-term follow-up study in 1114 Finnish men, found that subsequent weight decrease among overweight patients and high CVD risk in midlife (mean age, 47 years) predicted the worst prognosis in late life (mean age, 73 years). However, Lavie et al 18 evaluated purposeful weight loss in 529 overweight and obese CHD patients and found that although 3-year mortality risk only trended lower for those who lost weight, several CVD risk factors and behavioral factors were markedly improved.…”
Section: Discussionmentioning
confidence: 96%
“…Alternatively, the paradoxical finding of a null relationship between WC and CVD risk and an inverse association between BMI and CVD seen even after exclusion of men with preexisting cancer and low renal function may reflect what is often seen in those with established CVD, commonly referred to as the obesity paradox. 27 Although men with established CVD and stroke were excluded, it is possible that many of these older men have subclinical CVD or pulmonary disease conditions in which the obesity paradox is often reported. Thus, subclinical disease in a proportion of men is likely leading to weight loss, particularly lean body mass, and so these men have low current BMI, whereas fat mass (and therefore leptin concentration) is less affected.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity contributes to the development of several cardiovascular (CV) risk factors, including hypertension, diabetes, metabolic syndrome, dyslipidemia, and obstructive sleep apnea, and may be an independent risk factor for coronary heart disease (CHD) [3]. However, large epidemiologic studies have shown that, compared to normal weight people, overweight and obese subjects with CV diseases, including CHD and following an acute myocardial infarction (MI), have better outcomes [4], a phenomenon known as the "obesity paradox" [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%